Design and Development of a Web-Based Audit Clearance Letter Application System Using PHP Framework at the Karanganyar Inspectorate - Wahyu Putri Sholefah; Nova Tri Romadloni (SMATIKA JURNAL : STIKI Informatika Jurnal, 2026)
This research aims to design and develop a web-based Audit Clearance Letter application system at the Karanganyar Regency Inspectorate using the Laravel framework and MySQL database. The previous manual administrative process caused delays in verification, difficulties in tracking application status, and risks of data recording errors. This study adopted the Research and Development (R&D) methodology in conjunction with the Waterfall development model, which encompasses five sequential phases: requirements specification, system design, implementation, verification, and operational maintenance. The architectural foundation of the system was established upon the Model-View-Controller (MVC) pattern, selected to ensure a more organized, secure, and sustainable application structure. The results indicate that the system successfully integrates application submission, document upload, verification, letter issuance, and real-time status tracking within a single digital platform. Black Box Testing conducted on 14 testing scenarios achieved a 100% success rate and improved administrative efficiency from 2–3 working days to less than 1 working day in the verification and document monitoring process. In addition, User Acceptance Testing (UAT) achieved a User Satisfaction Index (USI) score of 88.2%, categorized as “Very Satisfactory.” The novelty of this research lies in the integration of a web-based Audit Clearance Letter administrative service specifically designed to improve transparency and efficiency in government supervisory institutions.